2015
DOI: 10.1016/j.aca.2015.04.054
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the settling of the resin beads on diffusion gradients in thin films measurements

Abstract: Binding resin beads used in DGT (diffusion gradients in thin films) tend to settle to one side of the resin during casting. This phenomenon might be relevant for metal accumulation when partially labile complexes dominate the metal speciation, especially after recognizing the important role played by complex dissociation in the resin domain. The influence of the inhomogeneity of the binding agent distribution on metal accumulation is here assessed by numerical simulation of DGT devices with binding beads in on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…). As it can be shown that the lability degree is -among others-a function of the free ligand concentration [46], the obtained lability degrees are plotted against the free oxalate concentration in Fig 3 . Given the dispersion of results, the lability degree of indium-oxalate complexes can be considered practically constant (despite some decrease could be predicted for increasing ligand concentration [47]). In principle, ξoxalates is expected to be a function of all conditions, pH included, because -for instance-the relative composition of the mixture of sequential complexes changes with pH (see eqn.…”
Section: K ξ ′mentioning
confidence: 99%
“…). As it can be shown that the lability degree is -among others-a function of the free ligand concentration [46], the obtained lability degrees are plotted against the free oxalate concentration in Fig 3 . Given the dispersion of results, the lability degree of indium-oxalate complexes can be considered practically constant (despite some decrease could be predicted for increasing ligand concentration [47]). In principle, ξoxalates is expected to be a function of all conditions, pH included, because -for instance-the relative composition of the mixture of sequential complexes changes with pH (see eqn.…”
Section: K ξ ′mentioning
confidence: 99%
“…Additionally, since the thickness of the region where the potential changes is much smaller than the thickness of the resin domain (where the electrostatic potential is mostly constant), a model that summarizes the electrostatic effects in a partitioning factor at the resin-gel interface is also used. The numerical solution of this model has been carried out in Fortran as explained in the SI of 30 . The checking of the accuracy of such model is of interest because it allows finding approximate analytical expressions in some cases 21 .…”
Section: The Partition Modelmentioning
confidence: 99%
“…The study of the physicochemical mechanisms that regulate the metal accumulation is essential for the interpretation of the DGT performance in varying environmental conditions (pH, ionic strength, etc.) [17][18][19][20]. However, the mechanisms that govern the kinetics of metal uptake by the free resin beads need further study.…”
Section: Introductionmentioning
confidence: 99%